KOMUNIKASI PERSUASIF LEADER DALAM MEREKRUT CALON AGEN ASURANSI PADA PT. PRUDENTIAL LIFE ASSURANCE CABANG PEKANBARU - Dina Siti Rahmawati; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The insurance company is a non bank financial institutions engaged in addressing the risk of that happening in the foreseeable future. In marketing its products, any insurance agent has power marketers who called with an insurance agent. Any insurance agent has a leader in the Agency's team in. Leader in charge of recruiting new agents using persuasive communication to change the attitude and behavior of prospective agents. This research aims to know the characteristics of the leader, the form of the message conveyed, the medium used, and communication techniques applied to leader in recruiting prospective insurance agents.This research uses qualitative methods with the descriptive approach. This research was conducted at PT. Prudential Life Assurance Pekanbaru Branch Pru Future Team, Tuanku Tambusai street peninsula complex block B, no. 8 Pekanbaru.. There are 6 participants were taken through a purposive sampling technique and snowball sampling technique. Types and sources of data obtained through the primary data and secondary data. Data collection is done with observation to participants, interviews and documentation. This research uses interactive data analysis miles and huberman with an examination of the validity of the data is done through the extension of participation and triangulation.The results of this research is showing that the characteristics of a leader should have in recruiting prospective insurance agents is the credibility and appeal. The form of the message is verbal and nonverbal messages. Media used namely face-to-face media and media brochures. and persuasive communication technique used is the search for common ground's point of view, do a comparison, asking and listening, communication style and build credibility.Keyword : Persuasive communication, recruitment, leader, insurance agent